1993
DOI: 10.1200/jco.1993.11.8.1441
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy after curative resection for gastric cancer: meta-analysis of randomized trials.

Abstract: In conclusion, at present, postoperative chemotherapy cannot be considered as standard adjuvant treatment. New trials of adjuvant therapy for gastric cancer must include a no-treatment control arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
190
0
13

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(206 citation statements)
references
References 0 publications
3
190
0
13
Order By: Relevance
“…Although most clinical trials investigating adjuvant chemotherapy generated inconclusive results (Hermans et al, 1993;Earle and Maroun, 1999;Cascinu et al, 2005), the trial by Cunningham et al (2005) (the MAGIC trial) has re-opened the debate about chemotherapy for operable gastric cancer patients. In this study, 503 patients affected by adenocarcinoma of the stomach, oesophagogastric junction or lower oesophagus were randomised to perioperative chemotherapy or surgery alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most clinical trials investigating adjuvant chemotherapy generated inconclusive results (Hermans et al, 1993;Earle and Maroun, 1999;Cascinu et al, 2005), the trial by Cunningham et al (2005) (the MAGIC trial) has re-opened the debate about chemotherapy for operable gastric cancer patients. In this study, 503 patients affected by adenocarcinoma of the stomach, oesophagogastric junction or lower oesophagus were randomised to perioperative chemotherapy or surgery alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although most clinical trials investigating adjuvant chemotherapy generated inconclusive results (Hermans et al, 1993;Earle andMaroun, 1999, Cascinu et al, 2005), it has been reported that a chemoradiotherapy adjuvant approach may improve the outcome of radically resected gastric cancer by lowering the incidence of local relapse (Macdonald et al, 2001).…”
mentioning
confidence: 99%
“…Studies over the past few years seeking to define the role of post-surgical adjuvant chemotherapy in gastric cancer have yielded contradictory results (de Braud et al, 1992;Atiq et al, 1993;Hermans et al, 1993), leaving the issue still unresolved. However, the modulation of 5-FU by folinic acid has led to the testing of promising new combinations in advanced gastric cancer (Murad et al, 1993;Neri et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis of patients with locally advanced gastric cancer is generally poor even with curative resection (Noguchi et al, 1989;Shiu et al, 1989;Fuchs and Mayer, 1995). Adjuvant chemotherapy has failed to demonstrate a significant survival benefit for such patients in most randomized trials and meta-analyses, except in a few studies with positive results (Shiu et al, 1989;Krook et al, 1991;Kim et al, 1992;Hermans et al, 1993;Nakazato et al, 1994;Fuchs and Mayer, 1995;Lise et al, 1995;Macdonald et al, 1995;Kelsen, 1996;Kim et al, 1998;Cirera et al, 1999;Earle and Maroun, 1999).…”
mentioning
confidence: 99%